TECHNOLOGY DEVELOPMENT ON THE USE OF DIMETHYL ETHER AS FUEL: A REVIEW (REVIEW PERKEMBANGAN TEKNOLOGI PEMANFAATAN DIMETHYL ETHER SEBAGAI BAHAN BAKAR) - Riesta Anggarani; I Made K Dhiputra; Cahyo S Wibowo; Dimitri Rulianto (Testing Center for Oil and Gas LEMIGAS, 2017)
Researchers have started focusing their research on alternative fuels. During the last two decades, Dimethyl Ether (DME) has emerged as a new potential fuel to substitute for oil and its derivatives. Raw materials for DME from sources such as coal, biomass, natural gas and also crude oil are spread all over the world so the interest is growing for using it as an energy source. While the technology for processing raw materials into DME is well established, the technology for DME applications for a wide range of usages is still being developed. The range of DME usage includes for automotive purposes, in industrial sectors, for household applications, and there is even fundamental research to discover more knowledge about DME safety and another technical considerations. Many research activities are now intensively being conducted in R&D centers and universities. This paper reviews progress in research activities that been used to develop the technology for DME application. Some opportunities for discovering more applications are also discussed in this paper. Penelitian mengenai bahan bakar alternatif menjadi fokus para peneliti di seluruh dunia. Dalam dua dekade ini, Dimethyl Ether (DME) muncul sebagai bahan bakar baru yang potensial untuk menggantikan bahan bakar minyak dan turunannya. Bahan baku DME yang bervariasi dari batubara, biomassa, gas alam dan juga minyak bumi menjadikannya menarik untuk dikembangkan sebagai sumber energi. Teknologi produksi DME dari beberapa bahan baku sudah tersedia secara matang, namun teknologi aplikasi DME untuk berbagai pemanfaatan masih terbatas. Pemanfaatan DME telah dilakukan pada berbagai sektor; otomotif, industri, aplikasi pada rumah tangga, dan bahkan juga penelitian fundamental untuk menggali pengetahuan yang lebih dalam tentang keselamatan penggunaan DME dan pertimbangan teknis lainnya dilakukan secara intensif di universitas serta lembaga –lembaga penelitian. Paper ini meringkas progress kegiatan penelitian yang telah dilakukan untuk mengembangkan teknologi aplikasi DME. Beberapa peluang untuk menemukan aplikasi baru didiskusikan dalam tulisan ini.